2013
DOI: 10.1002/jgrd.50853
|View full text |Cite
|
Sign up to set email alerts
|

Los Angeles Basin airborne organic aerosol characterization during CalNex

Abstract: We report airborne organic aerosol (OA) measurements over Los Angeles carried out in May 2010 as part of the CalNex field campaign. The principal platform for the airborne data reported here was the CIRPAS Twin Otter (TO); airborne data from NOAA WP‐3D aircraft and Pasadena CalNex ground‐site data acquired during simultaneous TO flybys are also presented. Aerodyne aerosol mass spectrometer measurements constitute the main source of data analyzed. The increase in organic aerosol oxidation from west to east in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…The smaller modes of rBC mass ( D VED_mode : 80–100 nm) and organic aerosol mass ( D M_mode : 150–160 nm) are consistent with the traffic emissions, particularly during morning rush hour traffic (Table ). The high mass fraction of smaller particles in Fontana could include contributions from SOAs (Craven et al, ). Chen et al () showed that, in Fontana, AMS‐VOOA mass was high in the afternoon, contributing more than 50% of organic mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The smaller modes of rBC mass ( D VED_mode : 80–100 nm) and organic aerosol mass ( D M_mode : 150–160 nm) are consistent with the traffic emissions, particularly during morning rush hour traffic (Table ). The high mass fraction of smaller particles in Fontana could include contributions from SOAs (Craven et al, ). Chen et al () showed that, in Fontana, AMS‐VOOA mass was high in the afternoon, contributing more than 50% of organic mass.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on sources and composition of aerosol particles in both SJV (Ahlm et al, ; Young et al, ; Zhang et al, ) and SoCAB (Chan et al, ; Craven et al, ; Hayes et al, ; Hersey et al, ) have mostly been limited to bulk PM 2.5 or PM 1 measurements. Only a few studies have reported high‐resolution size‐resolved compositions of aerosol particles with on‐line time resolution in these regions (Ensberg et al, ; Ge, Setyan, et al, ; Ge, Zhang, et al, ; Liu et al, ; Ying & Kleeman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Details about the PMF solution can be found in the supporting information. Numerous studies have utilized PMF to analyze AMS data [e.g., Ulbrich et al, 2009;Slowik et al, 2010;Chang et al, 2011;Hildebrandt et al, 2011;Hersey et al, 2011;Ng et al, 2011;Elsasser et al, 2012;Garbariene et al, 2012;Mohr et al, 2012;Craven et al, 2013]. Spectra can often be separated into just two categories-hydrocarbon-like organic aerosol (HOA) and oxygenated organic aerosol (OOA) [Ng et al, 2011].…”
Section: Mass Spectra Deconvolution Using Positive Matrix Factorizationmentioning
confidence: 99%
“…For the AMS on the G-1 aircraft, the 13 s detection limits of 0.3, 0.07, 0.05, and 0.15 µg m −3 for OA, SO 2− 4 , NO − 3 , and NH + 4 , respectively (Shilling et al, 2013), were higher because of the much shorter sampling period needed for aircraft operations. The detection limit for OA from the AMS on the CIR-PAS Twin Otter aircraft was reported to vary between 0.141 to 0.382 µg m −3 , depending on the flight (Craven et al, 2013) and is similar to the G-1. Observed and simulated composition concentrations are usually well above AMS detection limits, and thus the limits do not affect the model evaluation significantly.…”
Section: Carbonaceous Aerosolsmentioning
confidence: 92%
“…Four research aircraft, the NOAA WP-3D, the National Oceanic and Atmospheric Administration (NOAA) Twin Otter, the Center for Interdisciplinary Remotely Piloted Aerosol Studies (CIRPAS) Twin Otter and the NASA B-200, sampled atmospheric conditions aloft and the NOAA research vessel (R/V) Atlantis sampled atmospheric conditions along the coast of California. In situ measurements of meteorological, trace gas, and aerosol quantities were collected by the WP-3D (Bahreini et al, 2012;Ryerson et al, 2013;Langridge et al, 2012;Moore et al, 2012;Pollack et al, 2012;Warneke et al, 2011;Peischl et al, 2012), CIRPAS Twin Otter (Duong et al, 2011;Metcalf et al, 2012;Craven et al, 2013;Hersey et al, 2013), and the R/V Atlantis. The Tunable Optical Profiler for Aerosols and oZone (TOPAZ) differential absorption lidar (DIAL) was deployed on the NOAA Twin Otter (Langford et al, 2012) and the High Spectral Resolution Lidar (HSRL-1) (Hair et al, 2008) was deployed on the B-200 (Scarino et al, 2014).…”
Section: Measurementsmentioning
confidence: 99%